Edible plant Artemisia argyi H.Lév. & Vaniot: An in vitro study on its anti-Helicobacter pylori effect - Meiyun Chen; Sheng Pan; Fengli Lin; Weixing Zhu; Baojie Li; Bing Zhou; Guimin Zhang; Zhong Feng; Meicun Yao (Journal of Functional Foods)
A. argyi is a renowned herb widely used in food and medicine, offering significant economic benefits. H. pylori, a known carcinogen, is associated with numerous diseases. Current treatments primarily rely on antibiotics, but rising resistance has reduced their efficacy. The activity and mechanisms of A. argyi against H. pylori infection remain unclear. A. argyi exhibited strong bacteriostatic and bactericidal effects against multiple H. pylori. It demonstrated no antagonistic effects when combined with antibiotics and disrupted H. pylori morphology and structure, downregulated various virulence genes, and inhibited urease activity. In co-culture systems, A. argyi reduced H. pylori adhesion, urease levels, and NO production, indicating immunomodulatory activity. Among the five components of A. argyi with anti-H. pylori activity, jaceosidin exhibited the strongest effect (MIC: 10 μg/mL), followed by eupatilin. Methylation of jaceosidin reduced its anti-H. pylori activity. A. argyi is an edible herb with anti- H. pylori activity and excellent safety.